Program Bimbingan Sosial Pemberdayaan Remaja Korban KDRT dalam Meningkatkan Kepercayaan Diri PSAA Putra Utama 3 - Fauzan Ar Rizqy Haq; Wa Ode Asmawati (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This article discusses the social guidance program carried out by adolescent victims of domestic violence with the aim of increasing their self-confidence at Putra Utama Children's Home 3. In empowering these adolescents, PSAA Putra Utama creates a social guidance program, in which there are various approaches, including daily assistance, positive reinforcement, individual counseling, and skills training. The type of approach in this research uses descriptive qualitative methods, with data collection through in-depth interviews, observation and documentation studies. The results of the study revealed that the social guidance program carried out by PSAA Putra Utama 3 can improve. increase adolescents' self-confidence, which is reflected in progress in social interaction, personal motivation, and life goal setting. The adolescents showed significant improvements in adaptability and living a better social life. However, another thing that must be improved is regarding the indicators of the success of empowerment, PSAA Putra Utama 3 has not fulfilled having specific indicators to systematically evaluate the program. This research provides an overall picture of the success of the program and shows the need for the development of evaluation indicators to ensure the empowerment program can be further optimized.